2019
DOI: 10.1186/s12905-019-0840-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding what impacts on disclosing anal incontinence for women when comparing bowel-screening tools: a phenomenological study

Abstract: BackgroundThere is limited research defining the true prevalence of anal incontinence (AI) in women of childbearing age. Understanding the limitations of the current assessment tools in the identification of AI is paramount for identifying the prevalence of AI and improving the care and management for women of childbearing age. The aim of this research was to explore and develop an understanding of women’s experiences in disclosing AI when completing a new bowel-screening questionnaire when compared to two est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 27 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…There is evidence to suggest that care home residents with AI often have coexisting UI, known as double incontinence. 26 In population-based studies, UI has been found to coexist in 50% of patients with AI. 29 Risk factors for AI include: acquired structural abnormalities, for example secondary to childbirth and obstetric anal sphincter injuries; functional disorders, such as irritable bowel syndrome and inflammatory bowel disease; and neurological disorders, such as multiple sclerosis and dementia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence to suggest that care home residents with AI often have coexisting UI, known as double incontinence. 26 In population-based studies, UI has been found to coexist in 50% of patients with AI. 29 Risk factors for AI include: acquired structural abnormalities, for example secondary to childbirth and obstetric anal sphincter injuries; functional disorders, such as irritable bowel syndrome and inflammatory bowel disease; and neurological disorders, such as multiple sclerosis and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…10,25 Barriers in disclosing incontinence have been reported, including social expectations, the lack of a 'trusted space' for disclosure, confusion surrounding the medical terminology and meaning, and emotional, social and psychological consequences. 26 Reprinted. 5 Copyright 2020 John Wiley and Sons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The relationship between a woman and personal bowel function appears to be a largely private affair and it takes courage for some to discuss these concerns with health care professionals. 31 Fear and shame may lead women to find intuitive ways of managing their issue, such as digitation, without seeking a health care-initiated intervention. Digitation can be an uncomfortable process requiring good dexterity; it does not always work, and can present additional problems with co-morbidities or increased age.…”
Section: Introductionmentioning
confidence: 99%
“…Problems with low self-esteem are also often identified during clinical consultations 30 . The relationship between a woman and personal bowel function appears to be a largely private affair and it takes courage for some to discuss these concerns with health care professionals 31 . Fear and shame may lead women to find intuitive ways of managing their issue, such as digitation, without seeking a health care–initiated intervention.…”
Section: Introductionmentioning
confidence: 99%